2003
DOI: 10.1021/jm020886c
|View full text |Cite
|
Sign up to set email alerts
|

QSAR and the Rational Design of Long-Acting Dual D2-Receptor/β2-Adrenoceptor Agonists

Abstract: This paper describes the development of a QSAR model for the rational control of functional duration of topical long-acting dual D(2)-receptor/beta(2)-adrenoceptor agonists for the treatment of chronic obstructive pulmonary disease. A QSAR model highlighted the importance of lipophilicity and ionization in controlling beta(2) duration. It was found that design rules logD(7.4) > 2, secondary amine pK(a) > 8.0, yielded ultra-long duration compounds. This model was used successfully to guide the design of long- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 28 publications
3
42
0
1
Order By: Relevance
“…Indeed, whereas the released formoterol molecules were proposed to reach the receptor via classical three-dimensional (3D) diffusion within the aqueous phase, the more lipophilic salmeterol molecules were proposed to reach the receptor directly by two-dimensional (2D) diffusion within the plane of the membrane. Salmeterol should then be able to reach the active site of the receptor, which is located deep within its central cleft, by translocating between its transmembranespanning α-helical domains [25,26].In agreement with its very slow release from the tracheal strips (half-life~3 h), salmeterol also triggers persistent relaxation of this tissue in 'washout' experiments [27]. Interestingly, the relaxation diminishes swiftly when an excess of antagonist is added to the washout medium.…”
mentioning
confidence: 82%
“…Indeed, whereas the released formoterol molecules were proposed to reach the receptor via classical three-dimensional (3D) diffusion within the aqueous phase, the more lipophilic salmeterol molecules were proposed to reach the receptor directly by two-dimensional (2D) diffusion within the plane of the membrane. Salmeterol should then be able to reach the active site of the receptor, which is located deep within its central cleft, by translocating between its transmembranespanning α-helical domains [25,26].In agreement with its very slow release from the tracheal strips (half-life~3 h), salmeterol also triggers persistent relaxation of this tissue in 'washout' experiments [27]. Interestingly, the relaxation diminishes swiftly when an excess of antagonist is added to the washout medium.…”
mentioning
confidence: 82%
“…Using in vitro experiments this can be exhibited by 'wash-resistant' receptor activation, where signaling continues even after excess agonist is removed from the receptor by infinite dilution of the drug-containing buffer [8,9,[16][17][18][19][20][21][22]. It is anticipated that this could Thyroid-stimulating hormone SSIR >30 min a [9] Sphingosine-1 phosphate-1 SSIR; residence time and rebinding 300 min a Q6 [16,42] b2-adrenergic SSIR; exosite; membrane deposition >180 min a or >10 min b [25,27,43,44] Vasopressin-2 SSIR >40 min a [17] Glucagon-like peptide SSIR n.d. [37] Angiotensin-II SSIR >30 min b [45] Calcitonin a SSIR; residence time > 4320 min b [18] Serotonin 5-HT2B SSIR; residence time and rebinding >240 min a [19] GPR119…”
Section: Ligand Properties That Favor Persistent Receptor Interactionsmentioning
confidence: 99%
“…For dihydropyridines, it was proposed that such slow release allows their concentration within the membrane to remain above the therapeutic threshold for much longer than expected based on their plasma halflife [56]. In this respect, Austin et al [59] also insisted on the need to measure such release under physiologically relevant conditions, since they found that half-life for washout of the hydrophobic b 2 -adrenoceptor agonist salmeterol from tracheal Manifestations range from unlikely (-) to common (++). The general allosteric ternary complex model constitutes the simplest representation of allosteric interactions [20,104].…”
Section: Membranes Act As a Repositorymentioning
confidence: 99%